2014
DOI: 10.1515/jpm-2014-0105
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotocography patterns and risk of intrapartum fetal acidemia

Abstract: Isolated reduced variability is in most cases not a sign of hypoxia. If development of hypoxia is ruled out with one FBS, this pattern does not require monitoring with repetitive FBSs throughout labor. Late decelerations and severe variable decelerations increase the risk for intrapartum fetal metabolic acidemia to the same extent. The combination of these decelerations and tachycardia was associated with the highest rate of fetal metabolic acidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 32 publications
1
36
0
2
Order By: Relevance
“…We have previously shown that Doppler mode and scalp blood electrode signal acquisitions lead to different STV values, which could cause a systematic error in comparisons. Also, the findings of Agrawal et al 17 could be explained by the notion that reduced variability without any other pathological feature in the CTG trace is not associated with lactacidemia …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have previously shown that Doppler mode and scalp blood electrode signal acquisitions lead to different STV values, which could cause a systematic error in comparisons. Also, the findings of Agrawal et al 17 could be explained by the notion that reduced variability without any other pathological feature in the CTG trace is not associated with lactacidemia …”
Section: Discussionmentioning
confidence: 95%
“…This is a secondary analysis of a database including 1070 deliveries at Karolinska University Hospital in Stockholm, Sweden, during 2009‐2011, where scalp blood sampling had been performed during labor due to non‐reassuring FHR traces, according to the CTG guidelines from the Swedish Society of Obstetrics and Gynecology (SFOG) at that time (http://www.sfog.se/media/17094/ctg kort). In total, 2134 fetal scalp blood (FBS) lactate values were available for the analysis . Lactate concentrations were grouped into: <4.2 mmol/L = normal, 4.2‐4.8 = preacidemia, >4.8 mmol/L = acidemia, and >6.6 mmol/L (>95th centile) as severe acidemia .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the usefulness of fetal cerebral Doppler in the early stage of fetomaternal hemorrhage with reassuring fetal status indications on the CTG has not been well documented . Therefore, the accumulation of similar cases of progressive fetal hemorrhage is needed to confirm the characteristic changes in CTG findings and their difference from those of fetal hypoxia/anemia …”
Section: Discussionmentioning
confidence: 99%
“…8,9 Therefore, the accumulation of similar cases of progressive fetal hemorrhage is needed to confirm the characteristic changes in CTG findings and their difference from those of fetal hypoxia/anemia. 10,11 In 2017, we reviewed the CTG findings in 26 cases of fetomaternal hemorrhage with decreased fetal movements in Japan that resulted in adverse neonatal outcomes (neonatal death or cerebral palsy). 9,12 In 23 of them (88%), a nonreassuring fetal status, such as an adverse SHR pattern, was observed on CTG at the first obstetric consultation conducted based on the mother feeling decreased fetal movements; however, in the remaining 3 cases (12%), a reassuring fetal status was noted on CTG.…”
Section: Discussionmentioning
confidence: 99%